Enhancement of anodic oxidation of formic acid on Pd–Fe bimetallic nanoparticles by thermal treatment. (8th March 2021) - Liao, Mengyin; Li, Weiping; Peng, Jiaxi; Zhang, Fan; Xu, Wenyuan; Huang, Zhichao
Abstract: The surface composition and catalytic properties of Pd–Fe bimetallic catalysts with identical bulk composition can be continuously tuned by treatment at different temperatures. The activity of these catalysts in formic acid oxidation was related to the treatment temperature. The thermal treatment temperatures ranged from 400 to 600 °C. The Pd–Fe nanoparticles are characterized by an array of analytical techniques including TEM (transmission electron microscopy), XRD (X-ray diffraction), ICP (inductively coupled plasma) and HS-LEIS (low energy ion scattering spectroscopy). The electrocatalytic activity is examined using cyclic voltammetric and chronoamperometric measurements. The Pd–Fe/C catalyst with 500 °C shows the highest electrocatalytic activity for formic acid oxidation, with a current activity 3 times higher than that of before treated Pd–Fe/C catalyst, 5.6 times higher than that of commercial Pt/C catalyst. The migration of Pd to the surface on the nanoparticle catalysts as well as the electrochemical active surface area of the PdFe–H catalysts was shown to play a major role in enhancing the electrocatalytic activity for catalyst. These findings provided important insights into the correlation between the electrocatalytic activity and the treatment temperature of the nanoengineered bimetallic catalysts. Highlights: The Pd–Fe/C nanocatalyst was tuned by treatment at different temperatures. The Pd–Fe/C catalyst with 500 °C shows the highest electrocatalytic activity for formic acid oxidation. The size, outmost surface and catalytic activities of Pd–Fe nanoparticles can be varied with increasing temperatures. The PdFe–H catalysts can significantly reduce Pd use and thus cost.